Impact of the observers' experience on daily prostate localization accuracy in ultrasound‐based IGRT with the Clarity platform. (8th July 2014) - Fiandra, Christian; Guarneri, Alessia; Muñoz, Fernando; Moretto, Francesco; Filippi, Andrea Riccardo; Levis, Mario; Ragona, Riccardo; Ricardi, Umberto
Abstract : The aim of this study is to evaluate the accuracy of daily prostate localization with ultrasound imaging of various radiation oncologists with nonhomogeneous expertise. For ten patients who underwent radical radiotherapy for localized prostate cancer, 11 radiation oncologists reviewed daily ultrasound scans acquired during three different treatment sessions. The average values of two senior radiation oncologists, considered to be expert observers, were selected as reference. The remaining nine observers were divided into two groups, Group 1 and Group 2, with more and less than one year of experience, respectively. The recorded shifts in prostate position were divided in three classes: <3 mm, 3–5 mm, and > 5 mm. Deviations from reference were less than 3 mm in all directions in 91% and 81% of measurements in Groups 1 and 2, respectively. The maximum difference in terms of root mean square error (RMSE) was reported for superior‐inferior (SI) direction, in particular a mean difference of 3.24 mm was observed for Group 2 in respect to the reference; moreover RMSE was 1 and 1.3 mm higher for Group 2 for anterior‐posterior (AP) and left‐right (LR) directions, respectively. The difference between Groups 1 and 2 was significant (p < 0.01) for all directions. The mean values for the shifts in all three directions between Group 1 and the references were 0.235 mm, 0.385 mm, and 0.009 mm for the LR, SI, and AP directions, respectively. The position of the prostate gland is more easily detectable ( p = 0 . 02 ) in the AP direction, while the visibility is lower for LR ( p = 0 . 02 ) and SI boundaries ( p < 0.05). The observers' experience is essential for positioning the target correctly; therefore, a training period is recommended before putting the system into clinical practice. PACS number: 87.63.dh